GROWTH OF SEEDS (Eucalyptus pelita F. Muell) USING VARIOUS PLATING MEDIA - Rosianty, Yuli; Lensari, Delfy; Monita, Russindah Muhaajiroh (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2021)
Eucalyptus Sp is one type of priority which developed in the management of earmarked as a timber fibers estate .This research aims to review the results of the best combination of peat growing media, charcoal and cocopeat most good for growth seeds (E. pellita F.Muell). This study was conducted in November 2019 to January 2020. The methodology using patterns of random design group (RAK). Each treatment group consists of 3 treatment 9, 27 so there is any treatment that were taken 3 sample 81 seeds. Observation variables observed that is high in plant , diameter of the stem , number of leaves , a heavy wetness and heavy dry total , index the quality of seeds , and the percentage of life. The results of the data shows that the treatment of seeds (E. pellita F.Muell) real bearing on tall plants, trunk diameter, the number of, leaves a heavy wetness total, heavy and dry an index of quality seeds and live percentage. The results of the data shows that the treatment of seeds (E. pellita F.Muell) real bearing on tall plants, trunk diameter, the number of, leaves a heavy wetness total, heavy and dry an index of quality seeds and live percentage. Media growing season (peaty soil mixed cocopeat 1: 1) shows the results of that is better and the average rate of the most highest for growth seeds (E. pellita F.Muell) in tall plant , diameter of the stem , number of leaves , a heavy wetness and heavy dry total , index the quality of seeds. To the percentage lived in all media planting fly 100 % seeds no living the dead